Interpretasi Film Budi Pekerti: Antara Moral Dan Viral (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
The development of the world of cinema is currently growing rapidly, including in Indonesia. Various film themes have been produced as a means of entertainment and conveying messages to audiences. This research aims to describe the message conveyed in a film by analyzing the content qualitatively in the presentation of the story of the film "Budi Pekerti" which is a drama genre which will tell the story of a teacher who suddenly goes viral on social media. However, as a result of this, netizens' reactions turned out to endanger their careers and their families. The author discusses the initial problems studied regarding the delivery of a moral message and analyzes scenes from the film "Budi Pekerti", by applying the theory of semiotic analysis. The final result obtained by researchers is to know the forms of Cyberbullying and the moral messages in the film "Budi Pekerti".